Intercultural competence and leadership identity in blended global learning: Insights from Thai Undergraduate Students - Suengkamolpisut, Wallapa; Singhatong, Saifon; Viriyamano, Sithapan (Journal of International Students, 2026)
This study examines how Thai undergraduate students developed intercultural competence, leadership identity, and sustainability perspectives through a two-week blended international program. Using a qualitative design, data were collected from interviews with 24 students (16 nonparticipants and 8 participants) and from reflective journals. Thematic analysis revealed three developmental shifts: sustainability perspectives advanced from corporate social responsibility (CSR) and sustainable development goals (SDGs) framing to applied systems thinking; leadership identity evolved from aspirational to collaborative practice; and intercultural engagement deepened through adaptability, empathy, and confidence. The findings highlight the transformative potential of short-term blended programs in Southeast Asia and their alignment with SDGs 4, 12, and 13